The Relationship Between Community Attitudes and Mosquito Nest Eradication (Psn) Activities in Gampong Pusong Baru, Banda Sakti District, Lhokseumawe City - Rahmad Mouliansyah (International Journal of Health Engineering and Technology, 2025)
Abstract This study aims to determine the relationship between community attitudes and mosquito nest eradication (PSN) activities in Gampong Pusong Baru, Banda Sakti District, Lhokseumawe City. The research employed a descriptive correlational design with a cross-sectional approach. The population consisted of all residents of Gampong Pusong Baru, totaling 235 respondents. Data were collected using a validated questionnaire and analyzed using the Chi-Square test with a significance level of α = 0.05. The results showed that most respondents were aged 26–35 years (52.3%) and had a secondary education level (60.4%). Based on the analysis, there was a significant relationship between community attitudes and PSN activities, with a p-value of 0.000 < α = 0.05. Communities with positive attitudes were more likely to engage in PSN activities (38.7%) compared to those with negative attitudes (7.2%). It can be concluded that community attitudes play an important role in the success of PSN programs. Therefore, efforts to enhance knowledge and provide continuous education are necessary to foster positive community attitudes toward mosquito nest eradication, in order to prevent vector-borne diseases such as dengue hemorrhagic fever (DHF).